Bias Correction in Estimation of the Population Correlation Coefficient - Sinsomboonthong, Juthaphorn (Agriculture and Natural Resources, 2013)
An estimator of the population correlation coefficient of two variables for a bivariate normal distribution was proposed and evaluated using comparisons with the Pearson correlation coefficient and an estimator of Olkin and Pratt, conducted using a simulation study. It was found that for a small sample size of n=10, the absolute bias of the proposed estimator was less than those of the Pearson correlation coefficient and an estimator of Olkin and Pratt. In addition, the mean square errors of those estimators seemed to have no difference in each situation for this study.